Анализ базовых аддитивных технологий с учетом их основных технологических возможностей - Сердюк, Алексей Иванович; Кухарь, Владимир Валентинович; Присяжный, Андрей Григорьевич (НТУ "ХПИ", 2017)
Технология трехмерной печати по праву считается самым значительным прорывом XXI века. Технологическая эволюция трехмерного принтера создала новую область знаний – аддитивные технологии. Дискуссия о том, какая технология лучше, не имеет значения, так как у каждой из них есть целевые назначения. В статье выполнен анализ базовых аддитивных технологий с учетом их основных технологических возможностей и области применения. Даны рекомендации о предварительном выборе аддитивных технологий при изготовлении прототипов и готовых изделий.

The Three-Dimensional printing technology is considered the most significant breakthrough of the XXI century. The technological evolution of three-dimensional printer has created a new area of knowledge – additive manufacturing. Additive manufacturing are no longer used only for prototyping, but is increasingly used for the manufacture of the final product. To select a suitable technology developer needs to know the capabilities of these technologies. The aim of the article is analysis of the basic additive technologies based on their main technological features and fields of application in the manufacture of prototypes and finished products. Pre-selection of additive technologies in the production model or the finished product can be made on the basis of the following recommendations: for creating accurate models or finished products with the mechanical properties of the metal, it is advisable to apply the technology of SLS; in the manufacture of similar grades of products with mechanical properties of plastics industrial level it is recommended to apply the technology of SLA, and on a limited budget – FDM.
Analysis of basic additive manufacturing based on their primary technological capabilities
Keywords: аддитивные технологии; метод SLA; метод FDM; метод SLS; additive manufacturing; SLA; FDM; SLS